Atomically-thin two-dimensional sheets for understanding active sites in catalysis - Sun, Yongfu; Gao, Shan; Lei, Fengcai; Xie, Yi (Chemical Society reviews, 2015)
Catalysis can speed up chemical reactions and it usually occurs on the low coordinated steps, edges, terraces, kinks and corner atoms that are often called "active sites". However, the atomic level interplay between active sites and catalytic activity is still an open question, owing to the large difference between idealized models and real catalysts. This stimulates us to pursue a suitable material model for studying the active sites-catalytic activity relationship, in which the atomically-thin two-dimensional sheets could serve as an ideal model, owing to their relatively simple type of active site and the ultrahigh fraction of active sites that are comparable to the overall atoms. In this tutorial review, we focus on the recent progress in disclosing the factors that affect the activity of reactive sites, including characterization of atomic coordination number, structural defects and disorder in ultrathin two-dimensional sheets by X-ray absorption fine structure spectroscopy, positron annihilation spectroscopy, electron spin resonance and high resolution transmission electron microscopy. Also, we overview their applications in CO catalytic oxidation, photocatalytic water splitting, electrocatalytic oxygen and hydrogen evolution reactions, and hence highlight the atomic level interplay among coordination number, structural defects/disorder, active sites and catalytic activity in the two-dimensional sheets with atomic thickness. Finally, we also present the major challenges and opportunities regarding the role of active sites in catalysis. We believe that this review provides critical insights for understanding the catalysis and hence helps to develop new catalysts with high catalytic activity. Atomically-thin two-dimensional sheets can serve as an ideal model to disclose the role of active sites in catalysis.